1986
DOI: 10.1002/gps.930010106
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse and dementia

Abstract: Elderly outpatients on the register of the Alzheimer's Disease clinic at Johns Hopkins Hospital, Baltimore, were screened for alcohol abuse, the aim being to assess the r81e of alcohol in their dementia.Twenty one percent were found to be heavy drinkers or alcohol abusers, at some time in the past. Sixty-four percent of these had been actively drinking at the time of onset of first symptoms of the dementia. Clinicians need to be alert to the possibility that alcohol may be an aetiological factor in their elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Rains and Ditzler studied 383 men and women, 9% of whom had a history of heavy alcohol use (Rains, 1993). More recently, studies by King and by Smith and Atkinson both found the prevalence of heavy alcohol use to be 22% in patients presenting to a dementia clinic (King, 1986;Smith, 1994a). In one of the few studies of alcohol use among demented long-term care residents, Carlen and colleagues determined that 29% of 130 residents with dementia met criteria for ARD (Carlen, 1994).…”
Section: Clinical and Population Based Studiesmentioning
confidence: 97%
“…Rains and Ditzler studied 383 men and women, 9% of whom had a history of heavy alcohol use (Rains, 1993). More recently, studies by King and by Smith and Atkinson both found the prevalence of heavy alcohol use to be 22% in patients presenting to a dementia clinic (King, 1986;Smith, 1994a). In one of the few studies of alcohol use among demented long-term care residents, Carlen and colleagues determined that 29% of 130 residents with dementia met criteria for ARD (Carlen, 1994).…”
Section: Clinical and Population Based Studiesmentioning
confidence: 97%
“…Second, our subjects may have had poor recall of the extent of their alcohol consumption, or may have actively concealed it. Some evidence would suggest that higher rates of alcohol abuse in the elderly are obtained when near relatives, in contrast to patients themselves, are asked to supply the alcohol history (King, 1986b), although this is still a contentious issue. Unfortunately, as coinformants were not asked about alcohol, we cannot address this possibility.…”
Section: Cage Resultsmentioning
confidence: 99%
“…Although numerous studies have demonstrated the detrimental effect of alcohol on cognitive functioning, it remains unclear as to whether overall quantity consumed, length of time of heavy drinking or a combination of these is of critical importance (Shaw & Spence 1985). Three recent north American studies (King 1986, Smith & Atkinson 1993, Carlen et a/. 1994 report that in 21-24% of patients diagnosed with dementia, there was evidence that alcohol contributed to cognitive impairment.…”
Section: Alcohol and Mental Healthmentioning
confidence: 99%